0727 Age-related association of visceral adiposity with cardiometabolic disorders in mild-to-moderate sleep apnea. (25th May 2022) - Karagkouni, Efthalia; Vgontzas, Alexandros; Fernandez-Mendoza, Julio; Lenker, Kristina; Basta, Maria; Krishnamurthy, Venkatesh; Bixler, Edward
Abstract: Introduction: Visceral adiposity is a key predictor of both metabolic syndrome and obstructive sleep apnea (OSA). Both metabolic syndrome and OSA are associated with cardiometabolic disorders, however, the association of OSA with these disorders weakens in older adults. We compared the relative strength of the association between visceral adiposity vs. OSA with hypertension and diabetes and whether this association is stronger in middle-aged vs. older adults. Methods: A clinical sample of 148 adults (53.79±12.45y, 36, 5% female) with mild-to-moderate OSA (5≤AHI<30) underwent 8-hour polysomnography, a clinical history and physical examination, including measures of blood pressure and fasting glucose. Hypertension was defined as blood pressure ≥140/90mmHg or use of anti-hypertensive medication. Diabetes was defined as fasting glucose ≥100mg/dL or receiving treatment for diabetes, except insulin. Visceral Adiposity Index (VAI) was calculated within each sex using Amato et al (2010) standardized formulas based on waist, BMI, triglycerides and HDL cholesterol. Logistic regression models examined the association between VAI and AHI with hypertension and diabetes, while simultaneously adjusting for sex and stratifying by age. We also generated under the receiver-operating characteristics (ROC) curves (AUC) having hypertension and diabetes as outcomes and gender, age, BMI, AHI and VAI as independent variables. Results: VAI was associated with greater odds of having hypertension (OR=1.57, 95%CI=1.20-2.06, P=0.001) and diabetes (OR=1.27, 95%CI=1.02-1.57, p=0.031) compared to AHI (OR=1.05, 95%CI=0.98-1.13, p=0.185; and OR=1.07, 95% CI=1.00-1.14, p=0.690, respectively) in adults aged <60y. There was no association between VAI or AHI with hypertension and diabetes in adults aged ≥60y. Adding VAI to standard clinical factors (age, sex, and BMI) yielded moderately-good risk models for hypertension (AUC=0.73) and diabetes (AUC=0.70) in adults aged <60y, while suboptimal risk models (AUC=0.61 and 0.68, respectively) in adults aged ≥60y. Conclusion: These data indicate that visceral adiposity, but not AHI, is associated with cardiometabolic disorders in patients with mild-to-moderate OSA, an association that is stronger in middle-aged adults. Visceral obesity should be a priority in preventive/therapeutic interventions in young and middle-aged patients with OSA. These findings also further support that OSA in older adults is a distinctly different phenotype. Support (If Any):